2021
DOI: 10.3390/chemosensors9080222
|View full text |Cite
|
Sign up to set email alerts
|

Aptamer-Sensitized Nanoribbon Biosensor for Ovarian Cancer Marker Detection in Plasma

Abstract: The detection of CA 125 protein in buffer solution with a silicon-on-insulator (SOI)-based nanoribbon (NR) biosensor was experimentally demonstrated. In the biosensor, sensor chips, bearing an array of 12 nanoribbons (NRs) with n-type conductance, were employed. In the course of the analysis with the NR biosensor, the target protein was biospecifically captured onto the surface of the NRs, which was sensitized with covalently immobilized aptamers against CA 125. Atomic force microscopy (AFM) and mass spectrome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…oDNA molecular probes were covalently immobilized onto the APTES-modified surface of the sensor chip via DTSSP crosslinker using the technique reported in our previous papers [ 33 , 34 , 35 , 36 , 37 ]. The concentration of the oDNA probes in the immobilization solution, prepared using 50 mM potassium phosphate buffer (pH 7.4), was 1 μM.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…oDNA molecular probes were covalently immobilized onto the APTES-modified surface of the sensor chip via DTSSP crosslinker using the technique reported in our previous papers [ 33 , 34 , 35 , 36 , 37 ]. The concentration of the oDNA probes in the immobilization solution, prepared using 50 mM potassium phosphate buffer (pH 7.4), was 1 μM.…”
Section: Methodsmentioning
confidence: 99%
“…The analysis of the data obtained in these experiments has indicated that upon repeated analysis of one and the same sample, changes in the signal from the NS sensitized with probe #1 (Figure 9а) make up ~40%, while the signal was virtually unchanged in the case with the NS sensitized with probe #4 (Figure 9b). Thus, the previously developed technique for the regeneration of the SOI-NS sensor surface allows for the repeated use of the SOI-NS sensor chip in the analysis of biological fluids [33][34][35][36][37]. The experiment on the analysis of one and the same miRNA sample isolated from plasma of a patient with confirmed ASD diagnosis was being performed for two working days.…”
Section: Biospecific Detection Of Mirnas Isolated From Blood Plasmamentioning
confidence: 99%
“…The third advantage is that these biosensors allow one to detect the target analyte within ~15-20 minutes in a small sample volume [19]. Owing to these advantages, this type of biosensors has found its applications for highly sensitive real-time detection of a number of various types of analytes (such as nucleic acids, proteins, and viral particles) at low and ultra-low (femto-and subfemtomolar) concentrations, as was demonstrated in numerous papers [21][22][23][24][25][26][27][28][29][30][31][32][33][34]. This explains why this type of biosensors is so attractive for use in early revelation of various diseases in humans.…”
Section: Introductionmentioning
confidence: 98%
“…Promising methods include the detection of PC using nanotechnology-based biosensors [2,[33][34][35][36][37][38]. Among them, one should single out biosensors containing miniaturized chips "silicon-on-insulator"-based nanoribbon structures (SOI-NR biosensors) [2,[39][40][41][42][43][44][45][46][47]. These biosensors allow one to detect biological markers of human diseases in biological fluids at very low concentrations (<10 −15 M [42][43][44][45][46][47]), which correspond to early stages of cancer [15].…”
Section: Introductionmentioning
confidence: 99%